2015
DOI: 10.1021/acs.jpcc.5b03709
|View full text |Cite
|
Sign up to set email alerts
|

Metallization and Superconductivity in the Hydrogen-Rich Ionic Salt BaReH9

Abstract: BaReH 9 is an exceedingly high hydrogen content metal hydride that is predicted to exhibit interesting behavior under pressure. The high-pressure electronic properties of this material were investigated using diamond-anvil cell electrical conductivity techniques to megabar (100 GPa) pressures. The measurements show that BeReH 9 transforms to a metal and then superconductor above 100 GPa with a maximum T c near 7 K. The occurrence of superconductivity is confirmed by the suppression of the resistance drop on ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…High-pressure experiments found that the ternary hydride BaReH 9 is a superconductor with T c about 7 K at 100 GPa. 24 Also in theoretical work, the T c of Fe 2 SH 3 , 25 YS 4 H 4 , 26 and YSH 5 27 at 173, 200, and 300 GPa is about 0.3, 20, and 0.7 K, respectively. Earlier, through theoretical calculations, our group found that after the introduction of Mg in the insulating CH 4 system, the T c of MgCH 4 can reach 120 K at 121 GPa.…”
Section: Introductionmentioning
confidence: 91%
“…High-pressure experiments found that the ternary hydride BaReH 9 is a superconductor with T c about 7 K at 100 GPa. 24 Also in theoretical work, the T c of Fe 2 SH 3 , 25 YS 4 H 4 , 26 and YSH 5 27 at 173, 200, and 300 GPa is about 0.3, 20, and 0.7 K, respectively. Earlier, through theoretical calculations, our group found that after the introduction of Mg in the insulating CH 4 system, the T c of MgCH 4 can reach 120 K at 121 GPa.…”
Section: Introductionmentioning
confidence: 91%
“…Such achievements enhanced the interest in further searching possible room-temperature superconducting hydrides, and ternary hydrogen-rich compounds are interesting candidates. BaReH 9 was reported experimentally to be a superconductor under pressure, with a T c of about 7 K above 100 GPa [22]. Ba(AuH 2 ) 2 and Sr(AuH 2 ) 2 were predicted to be superconductors below 30 and 10 K at 1 atm, respectively [23].…”
Section: Introductionmentioning
confidence: 99%
“…There have been few studies on the superconductivity of compressed ternary hydrides [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Experimental examples include BeReH 9 [27] and Li 5 MoH 11 [28] synthesized under high-pressure conditions and showing unexpectedly low T c < 10 K. Crystal structure prediction simulations for ternary systems are computationally demanding.…”
mentioning
confidence: 99%